Investigating the communication network for batik village tourism stakeholders to support smart economy in Bogor regency, Indonesia - Roni Jayawinangun; Eneng Tita Tosida; Yogaprasta Adi Nugraha; Devanny Paradisa Aunnie; Deden Ardiansyah; Aceng Sambas; Jumadil Saputra (International Journal of Data and Network Science, 2024)
Unequal development is a major factor in measuring Indonesia's poverty problem, resulting in areas that are left behind. It is a primary concern of the government and stakeholders since it is unresolved and will lead to more problems in the community. Therefore, the government and stakeholders conduct various village developments to prosper the community. One is Batik village in Kemang, Bogor Regency, Indonesia. The Pakuan University of Bogor initiated the village development program. The collaboration forms a communication network and communication patterns to facilitate the delivery of messages. This study aims to identify and analyze the communication network pattern of stakeholders in the development of Kampung Batik in Kemang, Bogor Regency, Indonesia. This study is designed using a qualitative approach through interviews with relevant stakeholders. The communication network was analyzed using Sociometric Analysis through UCINET VI. The result indicates that the relationship between actors in the development of Kampung Batik is 75.5 percent and categorized as quite strong. Also, the communication pattern formed is an all-channel pattern with five actors who act as the star, bridge, opinion leader, liaison, cosmopolite, and isolate. This model supports the smart economy's potential to develop a smart village.